(untitled) (Research, Society and Development, 2020)
Diamantina, Minas Gerais, is contextualized as a municipal headquarters of the colonial nucleus, listed by IPHAN since 1938, and recognized as a Cultural Heritage of Humanity by UNESCO in 1999. This work aims to present a pedagogical itinerary through houses in the colonial centre of Diamantina, related to personalities born or who lived in the region and who had relevant life and work in different fields of knowledge. It was carried out based on bibliographic research and informal interviews with local historians. The result consisted of a selection of 9 characters, symbolized by the identification of the location of their homes. The data are in a folder with a script by the colonial core and the location of personalities houses. The back contains the primary information for each one. In this sense, work constitutes a differential in the relationship between heritage, heritage and collaborative education, teaching practices and for the society.